The 2 equations are
-2x + y = -17 ---1)
3x + y = 23 ---2)
we need to have the same coefficient for one of the variables.
Already y variable has the coefficient of 1 for both equations so we can use the equations as it is.
2) - 1) subtract 1) from 2)
3x-(-2x) + y -y = 23-(-17)
5x = 40
x = 8
substituting x = 8 in the 2nd equation
3*8 + y = 23
24 + y = 23
y = -1
solution - (8,-1)
5.65 in decimal and 113/20
Answer:
<h3>stay safe healthy and happy<u>.</u></h3>
Answer: 512 cm³
Explanation: Since the length, width, and height of a cube are all equal,
we can find the volume of a cube by multiplying side × side × side.
So we can find the volume of a cube using the formula v = s³.
In the cube in this problem, we have a side length of 8 cm.
So plugging into the formula, we have (8 cm)³
or (8 cm)(8 cm)(8 cm), which is 512 cm³.
So the volume of the cube is 512 cm³.